Prevalence of Celiac Disease in type 1 Diabetes Mellitus in children and adolescents attending Children Welfare Teaching Hospital - Abduljabbar, Hana A.; Matloub, Huda Y.; Yassin, Batool A. Gh. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: The association of celiac disease and type 1 diabetes mellitus is known worldwide due to shared auto immunological background, since celiac disease could present in diabetic patients with non specific symptoms or asymptomatically, periodic serological screening is necessary for early diagnosis.Objectives: To estimate the prevalence of celiac disease in children with type 1 diabetes.Patients and methods: A total of 152 children with type 1 diabetes attending the Children Welfare Teaching Hospital; 67 boys, 85 girls with mean age of 10.3 year± 3.7 and mean duration of diabetes 3.5years ±2.5, from May 2010 -May 2011 were screened for celiac disease using immunoglobulin A and G tissue transglutaminase (tTG) antibodies, immunoglobulin A endomysium antibody (EmA), and antiglutamic acid decarboxlase(Anti GAD) antibodies estimation.Results: Anti tissue transglutaminase antibody was positive in 25 patients, more in girls (68%), duodenal biopsy was done for 15 patients, 13 had histological changes of celiac disease, making the prevalence of celiac disease 8.6%. The classical presentation of the disease was lacking in most patients, but they presented with short stature which was below the third percentile in 79% of patient with celiac disease. In most cases Celiac disease was diagnosed within the first year of the diagnosis of diabetes.Conclusion: Annual autoantibody screening is recommended, for early diagnosis and management of patients with diabetes type 1.